STRATEGI PEMASARAN DALAM MENINGKATKAN VOLUME PENJUALAN - Amanda Ridho Ivanza; Muhamad Iqbal Fasa (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Marketing Strategy is a form of a company's plan in the field of marketing to obtain optimal results in increasing the company's sales volume. The purpose of this research is to find out what marketing strategies have been implemented. This research uses a qualitative approach method, where research emphasizes the aspect of in-depth data in order to obtain the quality of research. In a company, marketing strategy plays an important role in increasing sales within the company. Marketing strategies are implemented to help companies achieve sales targets with 3 components, namely Segmentation, Targeting and Positioning. The results of the research show that sales have not implemented an appropriate marketing strategy which has decreased quite drastically. This is based on the ineffective implementation of the marketing mix (4P) and the lack of set sales targets